Resurgence of cinema as cultural laboratory in malaysia: design exploration on cinema architecture to manifest film culture in the community - Gowd, Deepankursingh; Mohd Noor, Mohd Zairul; D’Silva, Jeffrey Lawrence (Human Resource Management Academic Research Society, 2023)
Malaysia is always known for its plethora of cultures, traditions, and identity. Similarly, so does its cinema industry which has been existing for almost a century. The cinema theatre was a place and space where people of all ages meet and engage for entertainment. As the audience keeps growing, cinema halls are moving in shopping malls where more modern and bigger halls are being built to amuse people in both shopping and entertainment and the cinema theatre are closing down. These theatres were once an integral part of the urban fabric of the community and country. So, the architecture of the cinema provides a character, identity, and culture where which it acts a catalyst to socially sustainable society. To address this, architecture and cinema are used as two integral elements of sustainability principles on the social dimension consisting of equity and social identity, aesthetic, and comfort. A literature review was carried out using various databases to explore solutions to the questions posed in the study. The study presents a conceptual framework for a new cinema architecture which aims to reintroduce the cinema theatre as a cultural laboratory for the present and future generations and give a new perspective to the way of how the cinema theatres outside the shopping malls is. In summary, the study presents research on a new approach to cinema architecture and interaction with the urban fabric and community. The study demonstrates on how cinema theatre outside of shopping malls and the sustainability and criteria of cultural entertainment with the design of cinema theatre and operational guidelines and mechanisms to use in cinema architecture in the urban development and community.